MODERN STRATEGIES FOR THE DEVELOPMENT OF SCIENCE AND RESEARCHERS TRAINING: INTERNATIONAL EXPERIENCE - Yu. D. Artamonova; A. L. Demchuk; A. N. Karneyev; V. V. Safonova (Высшее образование в России)
Strategies for the development of science, technology and innovations at the turn of the 20th and 19th centuries, which assumed that the success of introducing innovations automatically leads to the growth of production, wages, and job, creating the conditions for subsequent investment, at present are subject to revision. The reason is not only the global crisis of the 2000s that led to the stagnation of science funding and to changes in its financing by the state, local authorities, business and outsourcing, but also longer-term trends in the development of modern society, in particular, the formation of the academic precariat, the attraction of scientific personnel to traditional centres of innovation (despite funding), and others. These trends are analysed in the article, as well as their implementation in the United States, the EU and China; the analysis is based on laws and other normative acts regulating R&D in those countries, as well as on statistical data. The main measures to support science and its development taken by governments and scientific centres of those countries are analysed. The article highlights major risks for modern science human resources development, that are associated with: (1) adequacy of personnel and their training for specific directions and research (for the difficulty of forecasting the staffing needs of specific areas of science and technologies); (2) high and multi-directional “entry requirements” for research activities; (3) the motivation for choosing an academic career (because of precarious nature of employment and wage fluctuations); (4) selection of the strategy for the development of science in the face of an increasing share of private funding, tough competition and focus on quick return; (5) commercialization of scientific research; (6) dilemmas of globalization (openness versus know-how, etc.).